Long-term safety and efficacy of recombinant factor VIII Fc fusion protein (rFVIIIFc) in subjects with haemophilia A - Nolan, B.; Mahlangu, J.; Perry, D.; Young, G.; Liesner, R.; Konkle, B.; Rangarajan, S.; Brown, S.; Hanabusa, H.; Pasi, K. J.; Pabinger, I.; Jackson, S.; et al. (Haemophilia : the official journal of the World Federation of Hemophilia, 2016)
Introduction The safety, efficacy and prolonged half‐life of recombinant factor VIII Fc fusion protein (rFVIIIFc) in previously treated patients with severe haemophilia A was demonstrated in the phase 3 A‐LONG and Kids A‐LONG studies. Here, we report interim safety and efficacy data from the rFVIIIFc extension study, ASPIRE (ClinicalTrials.gov #NCT01454739). Methods Eligible subjects could enrol in ASPIRE upon completing A‐LONG or Kids A‐LONG. There were four treatment groups: individualized prophylaxis; weekly prophylaxis; modified prophylaxis (for subjects in whom optimal treatment could not be achieved with individualized or weekly prophylaxis); and episodic treatment. The primary endpoint was development of inhibitors. Results A total of 150 A‐LONG subjects and 61 Kids A‐LONG subjects enrolled in ASPIRE. As of the interim data cut (6 January 2014), the median time on study was 80.9 (A‐LONG) and 23.9 (Kids A‐LONG) weeks. The majority of subjects (A‐LONG, 92.0%; Kids A‐LONG, 57.4%) had ≥100 cumulative rFVIIIFc exposure days. No inhibitors were observed. Adverse events were generally consistent with those expected in the general haemophilia A population. Median annualized bleeding rates (ABRs) were low with individualized [A‐LONG: 0.66; Kids A‐LONG: 0.00 (<6 years old), 1.54 (6 to <12 years old)], weekly (A‐LONG: 2.03) and modified (A‐LONG: 1.97) prophylaxis. There was no change in prophylactic infusion frequency or total weekly prophylactic dose in the majority of subjects from A‐LONG and Kids A‐LONG. Conclusion Interim data from ASPIRE confirm the long‐term safety of rFVIIIFc and the maintenance of a low ABR with extended‐interval prophylactic dosing in patients with severe haemophilia A.